De la matière historique à l’outil numérique : comment articuler le travail des historiens et des informaticiens avec les agences de développement logiciel ? - Manuelle Aquilina; Olivier Hû; Jean-René Ladurée (Humanités Numériques)
We look at the methods of cooperation between experts from the fields of history and computer science when setting up digital mediation systems in heritage structures (monuments, museums). Experts in history and information technology come together in the context of projects run by development agencies that are entrusted by cultural organisations with the task of developing digital mediation devices. Their working methods are very different, but they all have to work together to produce a technological container and its scientific content. During these exchanges, adjustments and negotiations, the researchers seem only to be called upon to produce raw data and concrete technical solutions, which sidelines the fundamental scientific issues. It seems to us that a number of factors affect the trade-offs that take place: the institutional context in which the system is set up, and the initial training and experience of the various people involved in these projects.